Accuracy Assessment of 3D Printed Casts Using Zirconia Fixed Implant prosthesis: A Comparative Study in the Anterior Maxilla - Abdeen, Layal. (Tufts University. Tisch Library., 2021)
Thesis (M.S.)--Tufts University, 2021.; Submitted to the Dept. of Posthodontics.; Advisor: Panos Papaspyridakos.; Committee: Yo-wei Chen, Aikaterini Kostagianni, Matthew Finkelman, and Aikaterini Papathanasiou.; Keyword: Dentistry.